How do stronger creditor rights impact corporate acquisition activity and quality? - Rainville, Megan; Unlu, Emre; Wu, Juan Julie (Journal of Banking & Finance, 2022)
We exploit a quasi-natural experiment (the adoption of state anti-recharacterization laws) to study the effect of strengthened creditor rights on corporate mergers and acquisitions. We find that, following the passage of anti-recharacterization laws, firms decrease overall acquisition activities. This effect is stronger for firms with worse agency problems. Announcement returns to shareholders are larger and post-merger operating cash flows are better for acquirers with weaker governance. Furthermore, returns to bondholders of these firms are also higher, indicating no wealth transfers. Taken together, our evidence suggests that ex-ante strengthened creditor rights can discipline firm managers to reduce value-destroying acquisitions and conduct higher quality deals.